The Role of Digital Media in Enhancing Waqf Governance: A Study on the Use of the X Platform by Waqf Institutions and Associations in Saudi Arabia - الاء بكر الشيخ (International Journal of Social Communication, 2025)
This study examines the role of digital media in enhancing the governance of waqf institutions through the X platform, using Media Richness Theory as a theoretical framework. A mixed-methods approach was employed, combining content analysis of eight waqf institutions’ accounts (four governmental and four non-governmental) over five months with a survey of employees in the waqf sector. The findings reveal that the platform contributes significantly to promoting transparency and community engagement, with awareness campaigns and interactive content being the most effective tools. The study concludes with practical recommendations for improving digital strategies in waqf institutions, while noting challenges in measuring the long-term impact of digital platforms on governance outcomes.